Effects of dilute acid pretreatment on chemical and physical properties of kenaf biomass - M. N. Nur, Aimi; Anuar, Hazleen; S. M., Nurhafizah; S., Zakaria (Taylor & Francis, 2015)
In the current research, kenaf represents an agricultural biomass that possesses enormous potential for industrial applications. Because of its complex structure, which is composed of cellulose, hemicellulose, and lignin, pretreatment process was conducted. Here, dilute acid pretreatment process was conducted, statistically using the response surface method, which included three parameters: mass of biomass (g), temperature (◦C), and time (min). About 2 g of kenaf biomass was treated with 2% dilute sulphuric acid, and it was found to have higher glucose conversion (25.3%) when the process was conducted for 60 min at the temperature of 180◦C. The main aim of the current research is to investigate the chemical and physical changes of kenaf biomass before and after the pretreatment. The changes could be clearly seen in the cellulose, hemicellulose, and lignin composition before and after the pretreatment, which were evaluated via TAPPI standard test methods. Morphological observation under scanning electron microscope confirmed the changes that took place on the kenaf biomass from complex to simple surface structure. Fourier transform infrared analysis confirmed the presence of cellulose, hemicellulose, and lignin contents of the kenaf biomass before and after pretreatment. Crystallinity of the treated kenaf biomass also increased from 46.6% to 70.0%, as evidenced from X-ray diffractometer analysis.